Dynamic control of APD optical detector for SONET receiver application - Fernandes, Brain Sunil Nicholas (2008)
In this dissertation, the design, characterization, control and deployment of such a receiver is investigated. The functionality of the communication link is monitored using Digital Communication Equipment, so as to ensure the operation of the controller over the entire range of the link application.